Penerapan Model Discovery Learning Untuk Meningkatkan Hasil Belajar Matematika Siswa - Hendri Nurmawan; Angga Pratama; Liana; Huriyah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
The aim of this research is to improve mathematics learning outcomes regarding fractions through the application of the discovery learning model. The type of research is classroom action research (PTK), with the subjects in this research being class II students at SDN 2 Pancor for the 2022/2023 academic year, totaling 26 students. I collected data from the research through observations and tests of each cycle. We completed the pre-cycle stage before starting the two-cycle research. Analysis of data on mathematics learning outcomes for fraction material shows that there is an increase in each cycle stage, where in the pre-cycle with a contextual approach, it is known that there are 3 students with low learning outcomes who do not meet the minimum criteria for completeness, and students with medium learning outcomes who are at the minimum completeness criteria are 2 people, and 12 students with high learning outcomes who exceed the minimum completeness criteria. Then, in cycle I, all students obtained high learning outcomes and exceeded the minimum completeness criteria. Meanwhile, in cycle II, there were 2 students with moderate learning outcomes who met the minimum completeness criteria, and 14 students with high learning outcomes who exceeded the minimum completeness criteria. The results of this research indicate that the application of the discoverylearning model can improve the mathematics learning outcomes of fraction material for class 2 students at SDN 3 Pancor.